2001
DOI: 10.1021/bi001608n
|View full text |Cite
|
Sign up to set email alerts
|

Interloop Contacts Modulate Ligand Cycling during Catalysis byEscherichia coliDihydrofolate Reductase

Abstract: As a continuation to our studies on the importance of interloop interactions in the Escherichia coli DHFR catalytic cycle, we have investigated the role of the betaG-betaH loop in modulating the closed and occluded conformations of the Met20 loop during the DHFR catalytic cycle. Specifically, to assess the importance of the hydrogen bond formed between Ser148 in the betaG-betaH loop and the Met20 loop, Ser148 was independently substituted with aspartic acid, alanine, and lysine. Moreover, the betaG-betaH loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 28 publications
3
90
0
Order By: Relevance
“…Previous kinetic studies of DHFR have revealed the important role played by the Met-20, FG, and GH loops in stabilization of the transition state and in control of substrate, product, and cofactor binding affinity and turnover (12)(13)(14). Our present relaxation dispersion measurements provide new insights into the mechanism by which millisecond time scale fluctuations of the active site loops, modulated by ligand-dependent changes in the relative stabilities of the major Met-20 loop conformations, are coupled to progression through the catalytic cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous kinetic studies of DHFR have revealed the important role played by the Met-20, FG, and GH loops in stabilization of the transition state and in control of substrate, product, and cofactor binding affinity and turnover (12)(13)(14). Our present relaxation dispersion measurements provide new insights into the mechanism by which millisecond time scale fluctuations of the active site loops, modulated by ligand-dependent changes in the relative stabilities of the major Met-20 loop conformations, are coupled to progression through the catalytic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic analysis of Met-20, FG, and GH loop mutants has confirmed their functional role in catalysis and in binding and release of cofactor, substrate, and products (12)(13)(14). The active site loops must cycle between the closed and occluded conformations at two steps in the reaction pathway, immediately after hydride transfer and again after product release; mutations that destabilize the closed conformation impair hydride transfer (13).…”
mentioning
confidence: 92%
“…E. coli BL21(DE3) cells containing the plasmid pET27b-bioseq-N18C-C85A-C152S-DHFR were grown at 37°C in NCZYM medium containing 50 mg͞liter kanamycin to an absorbance of Ϸ0.5 at 600 nm and then induced at 37°C for 5 h with 0.4 mM isopropyl-␤-D-thiogalactopyranoside. After harvesting, the bioseq-N18C-C85A-C152S-DHFR protein was purified by using established procedures involving methotrexate affinity and DE-52 anionexchange chromatography (6). Twenty milligrams of the purified DHFR (Ϸ50 M in 20 ml) was biotinylated in vitro at 25°C for 24 h in 50 mM potassium phosphate, pH 7.2, containing 1 mM DTT, 4 mM biotin, 5 mM ATP, and 0.5 mg of biotin ligase (BirA-H 6 ).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Kinetic parameters of the labeled enzyme were determined by previously established procedures (2,6). All ensemble thermodynamic and kinetic measurements were carried out at 25°C in MTEN buffer (50 mM Mes͞25 mM Tris͞25 mM ethanolamine͞100 mM sodium chloride), pH 7.0.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…10 Indeed, in recent years much debate has emerged regarding the role of protein dynamics in enzyme catalysis in general 5,11,12 and in DHFR, in particular. 6,[13][14][15][16][17][18] How protein dynamics might contribute to catalysis ranges from conformational gating, where conformational changes might even be rate limiting, 19,20 as is thought to be the case with DHFR, [21][22][23] to a much more speculative direct coupling of specific protein motions to the reaction coordinate, perhaps similar to the strong and selective Fermi resonance between the stretching and bending motions of C-H moieties. [24][25][26] Unfortunately, the study of protein electrostatics and dynamics has been limited by the challenges associated with the direct characterization of specific protein bonds, including their environment and motion.…”
Section: Introductionmentioning
confidence: 99%